2018
DOI: 10.1093/jscr/rjy177
|View full text |Cite
|
Sign up to set email alerts
|

Paraestomal hernia with gastric outlet obstruction: a case report and literature review

Abstract: An 69-year-old obese woman was submitted to an abdominoperineal resection (APR) with left side end colostomy to treat a synchronic sigmoid and middle rectum cancer. Six months after APR, she develop a PH with a progressive increase of the size. The patient refused the surgical indication. Thirteen years after APR she presenting with abdominal pain, hematemesis, bilious vomiting and non-functioning of the stoma in the last 2 days. She had a distended and painful abdomen without signs of peritoneal irritation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The majority of parastomal hernia patients were managed surgically and one patient was reported to be managed non‐operatively due to poor fitness for surgery. Relocation of stoma was identified in four patients while mesh reinforcement was noted to be more prevalent in recent reports with good post‐operative outcomes …”
mentioning
confidence: 87%
See 1 more Smart Citation
“…The majority of parastomal hernia patients were managed surgically and one patient was reported to be managed non‐operatively due to poor fitness for surgery. Relocation of stoma was identified in four patients while mesh reinforcement was noted to be more prevalent in recent reports with good post‐operative outcomes …”
mentioning
confidence: 87%
“…Relocation of stoma was identified in four patients while mesh reinforcement was noted to be more prevalent in recent reports with good post-operative outcomes. [7][8][9][10] Gastric outlet obstruction secondary to a parastomal hernia is rare. Literature review has demonstrated a greater risk in elderly females.…”
mentioning
confidence: 99%